EXTENSIVE LISTENING TO ASSIST YOUNG LEARNERS' L2 VOCABULARY LEARNING - Kukuh Dwi Pamuji, - (2021)
This case study reports on the implementation of extensive listening (EL) to assist the young EFL learners' L2 oral vocabulary learning. The focus of this study was placed on the students' L2 oral vocabulary gains after implementing EL and how they learnt L2 oral vocabulary via EL. This study involved seven students of the seventh grade of junior high school. They were selected purposively based on the results of the Listening Vocabulary Levels Test (LVLT) and the interviews with the English teacher. They then participated in a one-month period of EL program set up by the researcher. In the program, the students listened to four selected audio graded readers independently at their own pace and with the assistance of the researcher in virtual meetings via the Zoom platform. The students' learning gains were assessed with the pre- and post-test of the 60 target words taken from the audio graded readers they listened to. Meanwhile, their process of learning L2 oral vocabulary was scrutinized qualitatively using the data from the meetings' observations, supported with one-to-one personalized interviews with the students. The findings revealed that EL has contributed positively to the students' learning of L2 oral vocabulary, as shown in the results of their relative learning gains. However, the gains varied from subject to subject. In learning the L2 oral vocabulary via EL, the students made use of several resources available including the visual input, the textual input, the frequency of occurence, the pre-existing vocabulary knowledge, and the contextual clues both global and local. For the future EL program, considering those five aspects when implementing EL in the EYL pedagogy is thus necessary.